Outcomes following different upfront stem cell transplantation strategies for multiple myeloma: a statistical perspective on behalf of the Chronic Malignancies Working Party of the EBMT - Iacobelli, Simona; Schönland, Stefan; Koster, Linda; Blaise, Didier; Nicholson, Emma; Broers, A. E. C.; Chevallier, Patrice; Reményi, Péter; Folber, František; Gribben, John G.; Nur, Erfan; Rabin, Neil; et al. (Bone marrow transplantation, 2025)
Multiple myeloma (MM) is a heterogenous malignant disease. Novel agents including bispecific antibodies and chimeric antigen receptor (CAR) T cells have improved response rates and patient outcome, but the majority of patients ultimately still relapse. High dose chemotherapy followed by autologous hematopoietic stem cell transplantation (auto-HCT) remains standard care of treatment for transplant-eligible patients. While single auto-HCT is commonly used, a planned tandem auto-HCT or auto-allo approach remains controversial, based on conflicting results from clinical trials. Here we compared the outcome of 24,936 MM patients aged between 20 and 65 years who underwent first auto-HCT during 2002-2015, reported to the EBMT registry, of whom 3683 and 878 got tandem auto-HCT and auto-allo-HCT respectively. We used non-standard statistical approaches to account for time-dependence of treatments and of their effects, including models with multiple timescales and dynamic prediction. Differences were reported by graphs of hazard functions, hazard ratios and conditional probabilities over time. For both OS and PFS, there was a limited but persistent advantage for the tandem auto-HCT group compared to single auto-HCT, and a clear advantage for the auto-allo-HCT group over both other strategies in the longer term, albeit at the cost of higher early mortality.
Gesehen am 12.01.2026